Use Of Daily Journal Assessment in Early Childhood Learning - Maria Assy; Rivo Panji Yudha; Hamidah; Suarti; Jumiati (International Conferences on Early Childhood Education Proceedings, 2023)
Daily journal assessment is a type of narrative, flexible assessment sourced from authentic data on the real development of children that appears during learning and play activities. Daily journal assessment aims to enable teachers to plan, carry out data collection and analyze data in the daily journal. This study aims to describe how the use of daily journal assessment in early childhood learning. The informants in this study were 30 kindergarten teachers and principals in Baubau City. The method in this study uses a qualitative approach with a descriptive survey method, which is to find information about the use of assessments in early childhood learning used by teachers. In collecting data, the authors used observation techniques through interviews and documentation. The analysis used is data collection, data reduction, data presentation, conclusion and verification. Based on the results of identification in the field that the use of assessments, assessment implementation and assessment reporting that are widely used by teachers in early childhood learning are technical assessments of checklists, portfolios, and anecdotal notes. The use of daily journal assessments (narratives/diaries) is still not used by teachers as information on children's development while at school to parents. It is recommended for subsequent researchers to look for relationships in teachers' understanding of daily journal assessments and their application in the field.Keywords: Assessment, Daily Journal, Authentic, Learning, Early Childhood Daily journal assessment is a type of narrative, flexible assessment sourced from authentic data on the real development of children that appears during learning and play activities. Daily journal assessment aims to enable teachers to plan, carry out data collection and analyze data in the daily journal. This study aims to describe how the use of daily journal assessment in early childhood learning. The informants in this study were 30 kindergarten teachers and principals in Baubau City. The method in this study uses a qualitative approach with a descriptive survey method, which is to find information about the use of assessments in early childhood learning used by teachers. In collecting data, the authors used observation techniques through interviews and documentation. The analysis used is data collection, data reduction, data presentation, conclusion and verification. Based on the results of identification in the field that the use of assessments, assessment implementation and assessment reporting that are widely used by teachers in early childhood learning are technical assessments of checklists, portfolios, and anecdotal notes. The use of daily journal assessments (narratives/diaries) is still not used by teachers as information on children's development while at school to parents. It is recommended for subsequent researchers to look for relationships in teachers' understanding of daily journal assessments and their application in the field. Keywords: Assessment, Daily Journal, Authentic, Learning, Early Childhood